2019
DOI: 10.1007/s11136-019-02120-0
|View full text |Cite
|
Sign up to set email alerts
|

Meeting physical activity recommendations is associated with health-related quality of life in women before and after Roux-en-Y gastric bypass surgery

Abstract: Purpose Meeting physical activity (PA) recommendations is positively associated with health-related quality of life (HRQoL), but it is still unclear whether PA (specifically objectively measured) is associated with HRQoL in bariatric surgery candidates, both before and after surgery. Thus, the aim of this study was to examine the cross-sectional association between meeting objectively measured PA recommendations and HRQoL before and after Roux-en-Y gastric bypass (RYGB) surgery. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
3

Year Published

2020
2020
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 34 publications
0
14
0
3
Order By: Relevance
“…To the best of our knowledge, this is the first observational study that examined the relation between physical activity and HRQoL at more than 12 months post-bariatric surgery. Some previous studies assessed HRQoL and physical activity within the first year post-surgery ( 20 , 34 ), however a longer follow-up is needed to assess the effects of adopting a more active lifestyle. Our large cohort of patients with 2 years follow-up demonstrated that an increase in physical activity is related to greater improvement in both physical- and mental health.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first observational study that examined the relation between physical activity and HRQoL at more than 12 months post-bariatric surgery. Some previous studies assessed HRQoL and physical activity within the first year post-surgery ( 20 , 34 ), however a longer follow-up is needed to assess the effects of adopting a more active lifestyle. Our large cohort of patients with 2 years follow-up demonstrated that an increase in physical activity is related to greater improvement in both physical- and mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients rated their walking ability as ''very good'' or ''good,'' confirming one of the expectations of these patients for increasing their mobility. 17 Still according to the facets of the physical domain and specifically regarding the ability to perform after surgery, it was observed that most were satisfied with their ability to perform daily activities, with 20.4% considered good and 63.3% very good. Thus, regarding the ability to perform activities, it was evidenced that most are satisfied in the postoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…The expectations of patients undergoing bariatric surgery include feeling socially included and improving social, family, and work relationships. 17 The limitations of the study are the cross-sectional design, as well as the sample size of 49 women, in which we faced difficulties in capturing these patients in the postoperative follow-up. Such difficulty may have been due to overcoming the ''honeymoon,'' period as well as social and financial issues to travel to the service.…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity increases total energy expenditure and leads one year after bariatric surgery to a 4.2% greater BMI reduction and prevents weight regain within the first two years [23]. In addition, such interventions leads to a better preservation of muscle strength, muscle mass, endurance capacity, and bone mineral density, and a greater quality of life as will be discussed in the following paragraphs [24][25][26][27]. In final, in patients with obesity or other chronic diseases, physical activity levels independently relate to a lower risk for premature death, complications, need for hospitalization and other healthcare consumptions [28,29].…”
Section: Importance Of Physical Activity and Exercise Intervention After Bariatric Surgerymentioning
confidence: 99%
“…As a result, in the follow-up of patients after bariatric surgery, the assessment of physical activity and fitness, muscle strength and mass, and mineral bone density could be considered by clinicians. In addition, interventions aiming to improve this outcome parameters, lead to a better preservation of muscle strength, muscle mass, endurance capacity, bone mineral density, and a greater quality of life as will be discussed in the following paragraphs [24][25][26][27].…”
Section: Importance Of Physical Activity and Exercise Intervention After Bariatric Surgerymentioning
confidence: 99%